Panama : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper on Panama explores the current situation and trends of the Caja del Seguro Social (CSS) in Panama. The autonomy is embedded in its Organic Law, which also provides the agency with the right to have separate funds from the central government. The slowdown in economic activity and employment has led to a decline in the coverage of the social security system. The Panamanian pension levels are generous, despite the lack of indexation, even by the high standard of advanced European countries, and among the highest in Latin America.